A theological approach to the construction of houses of worship in Indonesia - Abdul Jamil Wahab; Mustolehudin; Abd Kadir Ahmad; Sitti Arafah; Joko Tri Haryanto; Setyo Boedi Oetomo; Kustini; Fakhruddin M (Cogent Social Sciences, 2024)
This study aims to explain the theological factor as the root of religious conflict in the construction of houses of worship. Many religious conflicts are studied from political, legal, or social factors but less elaborated theological dimension as a fundamental factor. The rejection of houses of worship is not only done by people of different religions but also by the internal religious community itself. One of the reasons for rejection is the theological dimension, namely religious views. This research uses a qualitative approach and data collection through interviews and literature studies. Important findings show there is no single factor in the conflict of building houses of worship. The rejection of houses of worship is usually motivated by complex issues, and one of them is a theological factor. Islamic jurists have different theological views; some are accommodative and moderate, and some are intolerant of the construction of houses of worship of other religions. This difference is due to the perspective of religious text and social context in determining Islamic law. The view of textualist theology encourages a less accommodating and even intolerant attitude toward the construction of other religions, even though administratively and state law is legal. On the other hand, the theological view of Islam also encourages the spirit of inclusivism, and even normatively, Muslims are commanded to respect places of worship of other religious groups.